2006
DOI: 10.1159/000090671
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Plasma Glucose after Lipid Changes in Mice Fed Fish Oil, Docosahexaenoic Acid, and Eicosapentaenoic Acid Diets

Abstract: Background/Aim: Effects of the dietary docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and fish oil on weekly changes in plasma glucose, total cholesterol, triacylglycerol, and phospholipid concentrations of male Crlj:CD-1 mice were investigated. Method: Animals were fed five different experimental diets which contained 6.0% lard (lard diet), 6.0% fish oil (fish oil diet), 1.5% DHA-ethyl ester + 4.5% lard (DHA diet), 0.4% EPA-ethyl ester + 5.6% lard (EPA diet), and 1.5% DHA-ethyl ester + 0.4% EPA ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Whether brain or circulating triacylglycerol levels are modifi ed by our dietary DHAenrichment regime remains to be explored. A longer period of DHA supplementation may be required, as suggested by the demonstration that -3-rich diets can lower plasma triacylglycerol (usually by 10-20%) in various strains of healthy mice but only after 4-16 weeks of supplemental -3 fatty acid intake (59)(60)(61).…”
Section: -3 -6 and -9 Metabolitesmentioning
confidence: 99%
“…Whether brain or circulating triacylglycerol levels are modifi ed by our dietary DHAenrichment regime remains to be explored. A longer period of DHA supplementation may be required, as suggested by the demonstration that -3-rich diets can lower plasma triacylglycerol (usually by 10-20%) in various strains of healthy mice but only after 4-16 weeks of supplemental -3 fatty acid intake (59)(60)(61).…”
Section: -3 -6 and -9 Metabolitesmentioning
confidence: 99%
“…Polyenoic fatty acids derived from fish oil (n-3 fatty acids) have been shown to decrease cholesterol absorption (20)(21)(22) and reduce plasma cholesterol in both animal models and humans (23)(24)(25)(26)(27)(28)(29). The mechanism for how fish oil-derived fatty acids interfere with cholesterol absorption is not clear.…”
mentioning
confidence: 99%
“…In previous studies, TG levels of in the livers of lard-fed mice increased or unchanged compared with those in fish oil-fed mice. 6,7,[14][15][16][17] Furthermore, several recent studies have found that accumulations of TG and fatty acid metabolites such as fatty acyl-CoA, DAG, ceramide, and glycosphingolipid are associated with hepatic steatosis and insulin resistance. [18][19][20] As for DAG, it has been reported that DAG levels were higher in subjects with nonalcoholic fatty liver disease (NAFLD), including nonalcoholic fatty liver (NAFL) and nonalcoholic steatohepatitis (NASH).…”
Section: ããmentioning
confidence: 99%
“…However, recent studies have found that the effects of fish oil on metabolic disorders are not limited to those of DHA and EPA. [5][6][7] A relatively high amount of palmitoleate (C16:1) is present in fish oil compared with other oils and foods. Thus, palmitoleate as well as n-3 polyunsaturated fatty acids might play roles in improving lipid metabolism by fish oil.…”
mentioning
confidence: 99%